The dyadic care experiences of elderly individuals with disabilities and caregivers in the home setting from the perspective of family resilience: A qualitative study - Abulaiti, Bahaerguli; Zhang, Xiangchun; Guan, Tingyu; Wang, Meng; Jia, Shoumei; Wang, Anni (Frontiers in Psychiatry, 2022)
Background: China is one of the most rapidly ageing countries in Asia, and nearly 90% of elderly individuals with disabilities choose to receive traditional, family-based, long-term care. A majority of family caregivers have insufficient care capacity and experience physical and emotional distress, which in turn affects the elderly. Objective: To describe the dyadic care experiences of elderly individuals with disabilities and their caregivers from the perspective of family resilience. Methods: A phenomenological research method was used. Semi-structured, in-depth, face-to-face interviews with 9 dyads of elderly people with disabilities and their families were conducted from August 2020 to February 2021. The Colaizzi method was used to analyse, summarize and refine the interview data. Results: The dyadic care experiences of elderly individuals with disabilities and their caregivers can be summarized in terms of two themes. Theme 1 is dyadic pressure, which includes the following subthemes: (1) substantial objective burden; (2) dual negative experiences, i.e., the perceived low value of elderly individuals and low positive gains by caregivers; and (3) dyadic emotional transmission. Theme 2 is dyadic cooperative coping, which includes the following subthemes: (1) adjustment of family beliefs, including by giving meaning to stress, maintaining a positive outlook towards the future and ensuring spiritual sustentation; (2) changes in family patterns, including flexible adjustment of family patterns and multichannel utilization of social resources; and (3) improvement of family communication, including effective information transmission, rational emotional expression and emotional connection, and cooperation to solve and prevent problems. Conclusion: Elderly individuals with disabilities and their family caregivers face multiple physical, psychological, and social difficulties and demands during daily care, in which context negative experiences exert influence on this dyad. They collaborate to exhibit family resilience via the adaptation and improvement of family beliefs, family patterns and family communication. The family as a unit expends a great deal of effort to adapt to conditions of stress in the context of caring and shows family resilience, which is closely related to the family’s cultural background and community situation. Dyadic resilience-based interventions can be developed based on core elements found by this study.